The Frontier in Paris: Artists from the American West in the French Capital, 1890–1900 - James R. Swensen (Transatlantica)
From 1890 to 1900 several artists traveled from the American West to Paris to advance their studies. Coming from the “wild West,” the French capital represented for them the most sophisticated city on earth. Interestingly, they found Paris to be a place of danger and adventure, a frontier of its own right. They also discovered that their European peers longed for images of a frontier West that included Native Americans, cowboys, and wild animals. Through their experiences in this new and exotic land, artists from Robert Henri to Cyrus Dallin learned that the frontier was more of a state of mind than an actual place.